Comparison of temporal and spatial variation of periphytic algal community in two urban lakes in Umuarama-PR (Brazil) - Godoy, Rodrigo Felipe Bedim; Andrade, João Gabriel da Silva; Ruggeri, Marcus Vinicius Ribeiro; Tavares, Lilian; Rocha, Anne Heloise; Santos, Marcela Barbosa dos; Rodrigues, Lucas Augusto Pereira; Porto, Carlos Eduardo; Nudi, Matheus Haddad; Crisiogiovanni, Enzo Luigi; Trevisan, Elias; Nascimento, Gilberto Soares (Ciência e Natura, 2022)
Water resources are very important for all living organisms, and as being of vital importance need to be preserved. Thus, many water bodies are monitored as an essential strategy for identification of possible alterations over space and time. The analyses were performed in two different hydrological conditions, and water sample and rocks were collected in two different points at each lake. The results showed higher values of Ammoniacal Nitrogen in Aratimbó Lake, mainly during dry period (Ammoniacal Nitrogen = 4.2 mgL-1) at P1. However, P2 at Tucuruvi Lake presented higher concentration of Orthophosphate (2.24 mgL-1). Total Periphyton density also demonstrated variation among the different hydrological scenarios and lakes. The Highest density was of 385.30 10³ ind.cm-2at Aratimbó Lake and 180.43 10³ ind.cm-2at Tucuruvi Lake in rainy condition. Comparing the predominance of species, In Aratimbó Lake, Chlorophyceae class was predominant at P1, while Cyanophyceae class was predominant at P2. In dry period, Bacillarophyceae class was seen as the predominant class for both of lakes and for all sampling points. Differently from Aratimbó Lake, in Tucuruvi Lake Bacillarophyceae class was predominant in both of hydrological scenarios.